Efeito da concentração de eu3+ e tb3+ na luminescência do y2o3 produzido pela rota sol gel utilizando matéria orgânica da água de rio - Santos, Naiara Silva dos (2024)
Luminescent materials have been increasingly investigated due to their great potential for applications in several areas, including the development of devices such as lasers, lamps and sensors. In this work, the development of undoped, doped and codoped yttrium oxide (Y2O3) with europium (Eu3+) and terbium (Tb3+) ions was investigated, to explore its luminescent properties and potential application in optical thermometry. In this sense, the search for conscious, low-cost production with property control has been gaining ground in recent years. To produce the material, the modified sol-gel route was used using humic substances from river water to produce nanomaterials. The samples were prepared and calcined at a fixed temperature of 1000 ºC, and the river source and dopant concentration were the parameters investigated in the initial part of this work.As reference material, samples were prepared by replacing river water with distilled water. Through XRD measurements, the cubic phase of Y2O3 was observed regardless of the solvent used, which indicates good reproducibility of the synthesis. The diffraction patterns of the doped and codoped samples did not show secondary peaks, which implies that the doping was successfully incorporated into the matrix. Photoluminescence measurements were performed, and the emission spectrum showed the characteristic peaks of Eu and Tb. For the excitation spectrum, several excitation bands were observed ranging from the ultraviolet (UV) region to the blue region of the visible spectrum, making this material a potential candidate for many applications, such as solar cells and thermometers. The codoped samples exhibited measured emission with the main and characteristic peaks of Eu3+ ( 5D0→7F2) e Tb3+ ( 5D4→7F5), with an optimized luminescent response when excited at 277 nm, especially at reduced concentrations of the two dopants (doped with 1% Eu and 1% Tb). There is an indication of energy transfer from Tb3+ ions to Eu3+, for these samples. Furthermore, it was observed that the main emission peaks of Eu3+ e Tb3+ are more sensitive to temperature variations, compared to the others, exhibiting a significant variation in their relative intensity. The results with temperature suggest a potential application as a luminescent thermal sensor.